Grindability, Grading and Wettability of Recycled Plaster - 李志新;彭家惠;赵海鑫;邱星星;赵敏 (Transactions of Tianjin University, 2016)
The changes of grindability, grading and wettability of recycled plaster(R-P)and the mechanisms of these changes were studied by using vickers hardness, particle size distribution(PSD), scanning electron microscope(SEM) and nitrogen adsorption porosimetry to reveal that R-P was obviously different from plaster of Paris(POP). At the same milling time, R-P had the characteristics of high specific surface area, fine particle diameterand uneven size distribution compared with POP, so R-P possessed both good grindability and poor grading. The water absorption, dissolution rate and mass loss in dry-wet cycle of the hardened recycled gypsum(hardened RG) increased, while the water saturated strength and dry-wet cycle strength decreased significantly compared with the hardened virgin gypsum(hardened VG). Therefore, poor wettability could be seen in R-P. The analyses indicated that the changes of grindability and grading could be attributed to the reduction in hardness and the increase in the porosity of hardened RG and that the poor wettability of R-P was caused by the increase of large pores and the changes of microstructure of hardened RG.